Which of the following expressions is NOT equivalent to (x − 6)(x − 3)?
A. (6 − x)(3 − x)
B. x(x) + (−6)(−3)
C. x2 − 3x − 6x + 18
D. x(x − 6) − 3(x − 6)

Respuesta :

Answer:

B. x(x) + (−6)(−3)

NOT equivalent  to (x − 6)(x − 3)

Step-by-step explanation:

(x − 6)(x − 3)

= x^2 - 3x - 6x + 18

= x^2 - 9x + 18

A. (6 − x)(3 − x)

= 18 - 6x - 3x + x^2

= 18 - 9x + x^2

= x^2  - 9x + 18  ---->equivalent  to (x − 6)(x − 3)

B. x(x) + (−6)(−3)  = x^2 + 18   ----> NOT equivalent  to (x − 6)(x − 3)

C. x2 − 3x − 6x + 18   = x^2 - 9x + 18  --> equivalent  to (x − 6)(x − 3)

D. x(x − 6) − 3(x − 6)

= x^2 - 6x - 3x + 18

= x^2  - 9x + 18  ---->equivalent  to (x − 6)(x − 3)